(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
The increasing influence of social media, online reviews, and customer ratings on purchasing decisions in the hospitality industry motivated this study. The aim was to analyze the effect of social media marketing, online customer reviews, and online customer ratings on the purchase decisions at Arthur Suites by Premier Hospitality Asia in Badung. The population consisted of all customers who made reservations through the Traveloka platform, totaling 359 individuals, with a sample of 78 respondents selected via simple random sampling. Data were collected using questionnaires and analyzed through multiple linear regression. The results indicated that, simultaneously, the three variables significantly affected purchasing decisions, with an R-squared value of 0.949. Partially, social media marketing, online reviews, and customer ratings each had a positive and significant impact on purchase decisions. The practical implication suggests that hotel management should enhance their online presence and interaction on social media and actively manage reviews and ratings to increase customer purchase intentions. The effective management of these factors can improve customer purchasing decisions and business success in the hospitality sector